Productivity Analysis of Draglines Operating in Horizontal and Vertical Tandem Mode of Operation in a Coal Mine-A Case Study - Rai P.; Yadav U.; Kumar A. (My University, 2025)
The tandem operation of draglines is in use in some of the major Indian opencast coalmines owing to the favourable geo-mining conditions, technical suitability, efficiency and economic viability. In view of the importance of tandem operation, the present study has been undertaken in a large Indian opencast coalmine in order to critically investigate the horizontal and vertical tandem operation of draglines on moderately strong and high sandstone benches (35-42 m), overlying a 15-18 m thick coal seam. The study has revealed that although the preparation of balancing diagram for planning of dragline operations is the first and the most important step, its actual implementation is equally important. Marked discrepancies in the productivity parameters as envisaged by the balancing diagram and as observed in the field studies, have been investigated and reported. The study also propounds the importance of appraisal of dragline productivity parameters, such as, cycle time, swing angle, seating position, availability, utilization, etc., in the field scale. Irrespective of the mode of operation (horizontal or vertical tandem), the study moots the concept of computation of the weighted cycle time and overall cycle time vis-à-vis swing angle variation for the draglines operating in field. The results drawn from the case study have been discussed in terms of cycle time computations, annual output computation and evaluation of earthmoving efficiency for the horizontal and vertical tandem modes of operation. © 2011 Springer Science+Business Media B.V.